2015
DOI: 10.33844/ijol.2015.60230
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of strategic leadership and empowerment on job satisfaction of the employees of Guilan University

Abstract: The methods for the management and leadership of educational and research organizations has always been a question of some researchers. With the emergence of the strategic management in educational organizations, different views were raised about the management of these institutions whether it is possible to apply issues related to the business and educational administration field. They both agree on the difference between educational environment and business environment. This difference leads to different res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…Leadership development strategies enhance the Generation Y employee's abilities, career development and align the employees with the strategies of the organization. Leadership development strategies include coaching, international assignment, and immediate feedback (Azbari et al, 2015). The researcher found that leadership career support provides the employee's learning and enhances the employ abilities that had a negative effect on the turnover intention (de Oliveira et al, 2019).…”
Section: Strategic Leadership and Intention To Staymentioning
confidence: 99%
“…Leadership development strategies enhance the Generation Y employee's abilities, career development and align the employees with the strategies of the organization. Leadership development strategies include coaching, international assignment, and immediate feedback (Azbari et al, 2015). The researcher found that leadership career support provides the employee's learning and enhances the employ abilities that had a negative effect on the turnover intention (de Oliveira et al, 2019).…”
Section: Strategic Leadership and Intention To Staymentioning
confidence: 99%
“…Gathering the two aspects of empowerment and performance, it is agreed that empowering employees can assist them in identifying the appropriate decisions that must be made for either the organization as a whole or their own department, giving them that -rather -strategic choice of empowerment will make them more capable of identifying weak points and working on them, as well as strength points and leveraging them. As agreed upon by Azbari et al (2015), this may aid in the development of more accurate results, which are typically the outcomes of empowerment accompanied with strategic management techniques.…”
Section: Employees' Empowerment Is the Way To Reach Better Performancementioning
confidence: 99%
“…Using a quantitative approach and a questionnaire distributed to a sample of (235) employees, as well as the use of structural equation modeling to analyze data, Azbari et al (2015) concluded that strategic leadership and empowerment increase employee satisfaction with the work environment and their overall satisfaction with their jobs. At the University of Muhammadiyah in Indonesia, Rustamadji and Omar (2019) conducted a research to see whether organizational commitment, a mediating factor in the relationship between strategic management and employee performance.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Strategic leaders chart the direction and future path of the organization that prioritizes perpetual learning cycles within the organization through various policies, regulations, and technology adoption. They practice participative decision-making, design the key strategies to achieve organizational goals, and empower their employees to implement those (Azbari et al, 2015). A string team of leadership in the management team will clearly articulate the organization's aims and communicate the means for their employees to achieve them.…”
Section: Learning Organization Job Satisfaction and Organizational Co...mentioning
confidence: 99%